IDENTIFIKASI SIFAT KIMIA TANAH PADA TANAMAN JERUK (Citrus sp.) KECAMATAN TIGAPANAH KABUPATEN KARO - Nani Kitti Sihaloho; Karel Sinar Malolikosa; Alex Wanson Munthe (Universitas Quality, 2023)
Identification of Soil Chemical Properties in Citrus Plants (Citrus sp.) Tigapanah District, Karo Regency. North Sumatra Province is one of the provinces in Indonesia where most of the population earns a living in agriculture, including citrus plants. This study aims to identify the chemical properties of the soil in Jeruk fields, to determine the condition of the land and determine recommendations for the management of Jeruk fields in Tigapanah District, Karo Regency. The research was carried out from December 2022 to March 2023 in Tigapanah District, Karo Regency. Soil test activities were carried out at the Research and Development Center Laboratory of PT. Nusa Pusaka Kencana Analytical & Oc. Bagulung Gardens Laboratory, Tebing Tinggi, North Sumatra. The end result of the entire series of analyzes mentioned above is the identification of chemical properties of Jeruk fields in Tigapanah District, Karo Regency and recommendations for land management to be carried out in order to increase the productivity of Citrus plants in Tigapanah District, Karo Regency. The chemical characteristics of the soil in Jeruk field, Tigapanah District, Karo Regency, namely soil pH is classified as neutral, base saturation is moderate, Cation Exchange Capacity is moderate, available-P is high and C-organic is high. The chemical fertility status of the soil in Jeruk fields in Tigapanah District, Karo Regency is classified as Medium.